Challenges in the Role of Gammaglobulin Replacement Therapy and Vaccination Strategies for Hematological Malignancy - Sánchez-Ramón, Silvia; Dhalla, Fatima; Chapel, Helen (Frontiers in Immunology, 2016)
Patients with chronic lymphocytic leukemia (CLL) and multiple myeloma (MM) are prone to present with antibody production deficits associated with recurrent or severe bacterial infections that might benefit from human immunoglobulin (Ig) (IVIg/SCIg) replacement therapy. However, the original IVIg trial data was done before modern therapies were available and the current indications do not take into account the shift in the immune situation of current treatment combinations and changes in the spectrum of infections. Besides, patients affected by other B cell malignancies present with similar immunodeficiency and manifestations whilst they are not covered by the current IVIg indications. A potential beneficial strategy could be to vaccinate patients at monoclonal B lymphocytosis (MBL) and monoclonal gammopathy of undetermined significance (MGUS) stages (for CLL and MM, respectively) or at B-cell malignancy diagnosis, when better antibody responses are attained. We have to re-emphasise the need for assessing and monitoring specific antibody responses; these are warranted to select adequately those patients for whom early intervention with prophylactic anti-infective therapy and/or IVIg is preferred. This review provides an overview of the current scenario, with a focus on prevention of infection in patients with hematological malignancies and the role of Ig replacement therapy.